Organizacja i wyniki gospodarstw bydlęcych i trzodowych - Mańko, Stanisław; Sass, Roman; Sobczyński, Tadeusz (Organization and Results of Cattle and Pig Farms, 2005)
Research is based on data received from farms maintaining agricultural bookkeeping in 2003 from all over the country. The organization and results of two kinds of farms are compared: those specializing in stock-breeding (2616) and pigs (1150). Pig farms obtain higher gross margin thanks to higher production intensity. However, this results in disturbing the rules of balanced production (too many animals and too big share of grain in crops) which may be dangerous to stabilization of the results in future.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 67-74